Bright and fast scintillation of organolead perovskite MAPbBr₃ at low temperatures - Mykhaylyk, V; Kraus, H; Saliba, M (Royal Society of Chemistry, 2019)
We report the excellent scintillation properties of MAPbBr3, an organic–inorganic trihalide perovskite (OTP). The characteristic scintillation time constants were determined using pulsed monochromatic 14 keV X-rays from a synchrotron. We find that between 50 and 130 K the MAPbBr3 crystal exhibits a very fast and intense scintillation response, with the fast (τf) and slow (τs) decay components reaching 0.1 and 1 ns, respectively. The light yield of MAPbBr3 is estimated to be 90 000 ± 18 000 ph MeV−1 at 77 K and 116 000 ± 23 000 ph MeV−1 at 8 K.